+0  
 
0
28
1
avatar

Fill in the blank with a constant, so that the resulting expression can be factored as the product of two linear factors.


3mn - 6m + 15n + ___

 Jul 9, 2021

Best Answer 

 #1
avatar+2116 
+1

3mn - 6m + 15n + a

mn - 2m + 5n + a/3

(m+5)(n-2) = mn - 2m + 5n - 10

mn - 2m + 5n + a/3 = mn - 2m + 5n - 10

a = -30

 

=^._.^=

 Jul 9, 2021
 #1
avatar+2116 
+1
Best Answer

3mn - 6m + 15n + a

mn - 2m + 5n + a/3

(m+5)(n-2) = mn - 2m + 5n - 10

mn - 2m + 5n + a/3 = mn - 2m + 5n - 10

a = -30

 

=^._.^=

catmg Jul 9, 2021

9 Online Users

avatar